Effect of concentration of aqueous alcohol solution and layer thickness on free convection due to local heating; Colloids and Surfaces A: Physicochemical and Engineering Aspects; Vol. 705 - Misyura S. Ya. Sergey Yakovlevich; Egorov R. I. Roman Igorevich; Zaitsev A. S. Aleksandr Sergeevich; Morozov V. S. Vladimir Sergeevich (2025, 2025)
Title screen